Smart Card Research and Advanced Applications 10th IFIP WG 8.8/11.2 International Conference, CARDIS 2011, Leuven, Belgium, September 14-16, 2011, Revised Selected Papers - Prouff, Emmanuel (Springer eBooks., 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 10th IFIP WG 8.8/11.2 International Conference on Smart Card Research and Advanced Applications, CARDIS 2011, held in Leuven, Belgium, in September 2011. The 20 revised full papers presented were carefully reviewed and selected from 45 submissions. The papers are organized in topical sections on smart cards system security, invasive attacks, new algorithms and protocols, implementations and hardware security, non-invasive attacks, and Java card security.